(untitled) (Italian Journal of Public Health, 2009)
Slovenia put forth cancer as the main topic for its Presidency to the Council of the European Union. This paper describes the process, which led to the adoption of the Council Conclusions on cancer in June 2008.The process included the production of two policy dialogues, a book on cancer, a conference on cancer and the Council’s conclusions, which aim to inform EU health policy in the field of cancer. As a problem of growing public health importance, cancer needs to be addressed on the four levels, which cover its key elements – primary prevention, screening, integrated cancer care and research. These should become parts of a consistent national strategy to address cancer in developing a national cancer plan based on a common EU strategy for an integral approach to cancer management.